Composing storylines of possibilities : immigrant and refugee families navigating school - Strickland, Martha J. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"In this book, internationally migrant families invite us to listen to the storylines of their mostly muted voices as they navigate the local schools in their new cultural context. They call us to hear them as they grapple with issues they encounter. They implore us to feel like an outsider and see the school as a foreign culture with language and communication barriers. The book is organized to enhance this carework. Each chapter begins with a vignette that includes the voices of one or more members of international migrating families, while introducing the context of the chapter. At the end of each chapter readers will find specific implications to consider. These are constructed with preservice teachers, practicing teachers, and educational administrators in mind. As you read each chapter, there is the call for school transformation. The families in this book entreat school personnel to engage with international migrant families and to embrace a risk and resilience model as we strive together for success. These storylines challenge us to examine our personal storylines for biases and deficit understandings and call us all to purposefully rewrite these in the spirit of possibilities as the families in this book have embodied for us"-- Provided by publisher.
Keywords: Refugees -- Education.; Immigrants -- Education.; Education -- Parent participation.; Multilingual education.; Educational change.; Community and school -- United States.; Education -- Educational Policy & Reform -- General.; Educational strategies and policy.; elektronické knihy; electronic books